TEOLOGI PENDERITAAN KONSTRUKTIF DALAM KONTEKS SOSIAL RELIGIUS DAN MASYARAKAT POSTMODREN - Mase, Boyes Agustina; Natalia (STT-RAI Batam, 2025)
This research explores the constructive theology of suffering within social and religious contexts, aiming to develop a contemporary understanding of suffering from a Christian perspective. Utilizing a qualitative methodology, the study draws on biblical texts and relevant literature, employing both constructive and systematic theological approaches. The findings reveal that suffering, often associated with sin and its consequences, is a complex phenomenon encompassing personal, social, and spiritual dimensions. The research examines various theological perspectives on suffering and investigates the concept of suffering within social contexts. Ultimately, the study proposes a framework for a constructive theology of suffering, drawing on biblical narratives, particularly the book of Job, and the example of Jesus Christ's suffering. This framework emphasizes the potential for suffering to deepen one's relationship with God, foster moral reflection, and strengthen social bonds. The conclusion highlights that a constructive theology of suffering offers a transformative perspective on this challenging human experience, underscoring its potential for spiritual growth, character development, and social solidarity.